Impact of an integrated seismic data processing approach - Semaan, Mars E. (1992)
Results from an integrated seismic data processing approach are presented. The following five industry known techniques are used: The first is pre-stack processing and imaging that resulted in properly placed structures and clearly defined fault planes. The second is wavelet processing which insured that the true responses of the reflectors are obtained. The third is inversion for the acoustic impedance which involves mapping the physical structures and properties of the subsurface. The fourth is amplitude versus offset (AVO) inversion using the Zoeppritz equations to determine the relationship between the P-wave and S-wave velocities, and Poisson's ratio. This method is used to infer lithological information, leading to a more accurate interpretation. The fifth is an event specific AVO inversion technique based on the fact that for a given porous lithologic unit, the behavior of the P-wave reflection amplitudes versus offset will vary depending on whether the pore spaces are filled with water, oil or gas. Data examples show that the above mentioned integrated seismic approach increased the interpreter's confidence of the prospect and led to a successful drilling program.